Love that works : the art and science of giving - Brander, Bruce (Templeton Foundation Press, 2004)
This original, highly readable book poses a clear distinction between our customary form of love, which almost guarantees failure, and higher, more generous ways of loving that can succeed and enrich both individuals and society as a whole. Love That Works draws on history, psychology, and the theology and science of love to offer a proposal on how to be successful in love and romance. It starts by showing why love fails to meet expectations, often ending sadly or even tragically.